Synergistic impacts of nutrient enrichment and climate change on long‐term water quality and ecological dynamics in contrasting shallow‐lake zones. Issue 9 (23rd June 2021) - Lin, Qi; Zhang, Ke; McGowan, Suzanne; Capo, Eric; Shen, Ji
Abstract: Anthropogenic and climatic stressors on freshwater ecosystems are of global concern. However, the interactions and effects of multiple stressors (e.g., nutrient enrichment, climate warming, altered wind and precipitation) acting over different spatial and temporal scales are often complex and remain controversial. Here, we reconstructed one‐century dynamics of eutrophication and primary producer communities in algal‐dominated and macrophyte‐dominated zones of a large shallow lake (Taihu, China), by integrating sedimentary photosynthetic pigments and geochemical records with water monitoring and historical archives. We aimed to explore the long‐term underlying mechanisms of the responses of water quality and lake biota to multiple environmental perturbations. We found that water quality degradation and algal community modification showed similar trends but distinct timings and trajectories in contrasting ecological zones. Onset and intensity of eutrophication in north Meiliang Bay (since the 1950s) exceeded far beyond that of macrophyte‐dominated Eastern Taihu (~1990s). Anthropogenic nutrients overtook past climatic control on production and composition of phototrophic assemblages. More importantly, lake phytoplankton responded markedly to climate warming, decreasing wind speed, and extreme weathers after cultural eutrophication. Synergistic interactions of nutrients and climate on lake ecosystems became increasingly significant in promoting harmful algal blooms (HABs) dominated by Microcystis, close to the hyper‐eutrophic north lake zones. The asynchronous limnological and ecological responses also indicated the modulating roles of lake ecological regime and catchment hydrogeomorphic characteristic. Collectively, our findings suggest that mitigation of eutrophication and HABs calls for a triple management strategy integrating anthropogenic nutrients, climate change, and lake‐catchment setting.